2018
DOI: 10.1016/j.jpeds.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Screening in the US May Miss Mild Persistent Hypothyroidism

Abstract: There is variation in NBS practices for screening for congenital hypothyroidism across the US, and many programs do not adjust the TSH cutoff beyond the first 2 days of life. Samples are processed when received from older infants, often to retest borderline initial results. This approach will miss congenital hypothyroidism in infants with persistent mild TSH elevations. We recommend that all NBS programs provide age-adjusted TSH cutoffs, and suggest developing a standard approach to screening for congenital hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 24 publications
1
37
0
1
Order By: Relevance
“…1 Similar increases have been observed in Western Australia (from 0.17 cases per 1000 births between 1981 and 1987 to 0.35 cases per 1000 births between 1988 and 1998) 2 and Italy (from 0.33 cases per 1000 births between 1987 and 1998 to 0.51 cases per 1000 births between 1999 and 2008). 10 Potential explanations for this observation include changes in population ethnic composition, 3 environmental changes (such as perchlorate exposure), 11 iodine deficiency, 12 and changes in clinical practice 13 and awareness that lead to better detection. Many screening programs' cutoff levels have changed over time, which may partially explain the increased case ascertainment rate.…”
Section: Congenital Hypothyroidism (Cht)mentioning
confidence: 99%
“…1 Similar increases have been observed in Western Australia (from 0.17 cases per 1000 births between 1981 and 1987 to 0.35 cases per 1000 births between 1988 and 1998) 2 and Italy (from 0.33 cases per 1000 births between 1987 and 1998 to 0.51 cases per 1000 births between 1999 and 2008). 10 Potential explanations for this observation include changes in population ethnic composition, 3 environmental changes (such as perchlorate exposure), 11 iodine deficiency, 12 and changes in clinical practice 13 and awareness that lead to better detection. Many screening programs' cutoff levels have changed over time, which may partially explain the increased case ascertainment rate.…”
Section: Congenital Hypothyroidism (Cht)mentioning
confidence: 99%
“…There is currently no agreement on the optimal whole-blood TSH concentration to be used as a cut-off for CHT screening; significant variation is seen in cut-offs used between NBS programmes [12], but our data show that using a threshold of 8 mU/L instead of 10 mU/L will identify infants with decompensated and permanent CHT. International consensus guidelines [3] recommend starting treatment immediately if venous thyroxine concentrations are below the reference range for age, and this was seen in 13 (40%) of the infants with initial whole-blood TSH concentrations between 8 and 9.9 mU/L.…”
Section: Discussionmentioning
confidence: 86%
“…In 2006, a study of Irish pregnant women suggested a prevalence of iodine deficiency of 55% in women tested in summer and of 23% in women tested in winter [14]. Higher TSH concentrations are seen soon after delivery [15], and the timing of screening influences the distribution of whole-blood TSH concentrations [12]. Thus, a cut-off of 8–9.9 mU/L is likely to identify more falsely elevated TSH concentrations if applied to a NBS programme that performs initial screening before day 3.…”
Section: Discussionmentioning
confidence: 99%
“…TSH concentrations continue to fall beyond the first days of life and are typically within the normal childhood range by one month of age. A recent US report highlighted the risk of missing children with mild persistent CH, given that the majority of programmes did not use age‐adjusted cut‐offs for repeat samples . Conversely, many programmes do apply lower cut‐offs for late samples, including the New Zealand programme that utilizes a lower threshold of TSH ≥8 mIU/L amongst repeat samples or those collected >14 days .…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, even a modestly lower threshold would reduce screen performance across the population as a whole (due to lower specificity and PPV highlighted the risk of missing children with mild persistent CH, given that the majority of programmes did not use age-adjusted cut-offs for repeat samples. 26 Conversely, many programmes do apply lower cutoffs for late samples, including the New Zealand programme that utilizes a lower threshold of TSH ≥8 mIU/L amongst repeat samples or those collected >14 days. 5 We excluded samples collected >7 days from our cohort as these would be anticipated to include a high proportion of repeat samples in babies with initially abnormal results, many of whom would subsequently be confirmed to have CH, and would therefore not be representative of TSH levels amongst the general population.…”
Section: Con Clus Ionsmentioning
confidence: 99%